Green Economy Paradigm Through the Lens of Local Wisdom: Connecting Tradition and Modernity in Sustainable Development - Hariyono; Hidayati, Umi; Suharto (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research Aim: This research aims to develop a conceptual framework that bridges the green economy paradigm with local wisdom, thereby achieving sustainable development. Design/Method/Approach: This conceptual research employs a constructivist approach, utilizing critical literature analysis and conceptual synthesis to develop a framework. Research Finding: The research findings present a conceptual framework that integrates green economic principles—namely, resource efficiency, emission reduction, and social justice—with elements of local wisdom, including traditional values, customary practices, and local ecological knowledge. The framework emphasizes the importance of integration mechanisms, including dialogue and collaboration, recognition and reward, adaptation and innovation, as well as justice and equality. Theoretical contribution/Originality: The theoretical contribution of this research is to offer a new perspective on the green economy by including a dimension of local wisdom, which is often overlooked in the mainstream literature Practical/Policy Implication: By practical implication, this framework can guide policymakers, development practitioners, and local communities in designing and implementing sustainable and inclusive green economy initiatives. Research limitation: The limitation of this study is that the conceptual framework developed is theoretical and requires further empirical validation.